2012
DOI: 10.1167/iovs.11-8463
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Spectrum Bias on the Diagnostic Accuracy of Spectral-Domain Optical Coherence Tomography in Glaucoma

Abstract: The effectiveness of most SD-OCT parameters in detecting glaucoma significantly decreased when evaluated against a clinically relevant control group with suspicious-looking optic nerves compared with that against a control group consisting of normal subjects with no findings suspicious for glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 37 publications
1
44
2
Order By: Relevance
“…Finally, our study's design was a case-control study including patients with well-established glaucoma, and using a separate group of normal subjects as hospital based-controls could overestimate the diagnostic performance substantially. 24,25 In conclusion, we demonstrated that the diagnostic performances of average cpRNFL thickness and average GCC thickness to identify early glaucoma and all-stage glaucoma were similar among Cirrus, RTVue, and 3D-OCT measurements in our study population. RTVue yielded a higher AUC value for nasal cpRNFL thickness than Cirrus and 3D-OCT in the detection of glaucoma.…”
Section: Discussionsupporting
confidence: 56%
“…Finally, our study's design was a case-control study including patients with well-established glaucoma, and using a separate group of normal subjects as hospital based-controls could overestimate the diagnostic performance substantially. 24,25 In conclusion, we demonstrated that the diagnostic performances of average cpRNFL thickness and average GCC thickness to identify early glaucoma and all-stage glaucoma were similar among Cirrus, RTVue, and 3D-OCT measurements in our study population. RTVue yielded a higher AUC value for nasal cpRNFL thickness than Cirrus and 3D-OCT in the detection of glaucoma.…”
Section: Discussionsupporting
confidence: 56%
“…We have recently demonstrated how a control cohort with no suspicious findings of glaucoma can affect the diagnostic ability of SDOCT parameters in glaucoma compared with a control cohort which is likely to be misinterpreted as glaucoma. 16 Due to the same reason, AUCs of RNFL parameters reported in our study are also lower compared with the studies that have reported the same with SDOCT 7,10,29 and GDx ECC 5,12,13,30 separately.…”
Section: Discussioncontrasting
confidence: 44%
“…This protocol has been explained earlier. 16,18 The RNFL parameters generated by the ONH protocol and used in the study were temporal average (temporal 90 degree), superior average (superior 90 degree), nasal average (nasal 90 degree), inferior average (inferior 90 degree), and global average (over 360 degree). The RNFL parameters are also compared with the internal normative database of 1081 subjects of different ethnicities within the software and one of the three diagnostic categorizations is provided.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…FLV measures focal loss using a pattern deviation map, similar to PSD in the VF. 38,39 We explored these parameters because some authors consider that MS-associated ON may share some pathogenetic, structural, and functional similarities with glaucomatous optic neuropathy. 33,35 Global and focal losses in the GCC map were significantly higher in the ON group compared with NON and control groups.…”
Section: Discussionmentioning
confidence: 99%